Street matters : a critical history of twentieth-century urban policy in Brazil - Lara, Fernando Luiz; Koury, Ana Paula (Pitt Latin American series., 2022)
"Street Matters links urban policy and planning with street protests in Brazil. It begins with the 2013 demonstrations that ostensibly began over public transportation fare increases but quickly grew to address larger questions of inequality. This inequality is physically manifested across Brazil, most visibly in its sprawling urban favelas. The authors propose an understanding of the social and spatial dynamics at play that is based on property, labor, and security. They stitch together the history of plans for urban space with the popular protests that Brazilians organized to fight for property and land. They embed the history of civil society within the history of urban planning and its institutionalization to show how urban and regional planning played a key role in the management of the social conflicts surrounding land ownership. If urban and regional planning at times benefited the expansion of civil rights, it also often worked on behalf of class exploitation, deepening spatial inequalities and conflicts embedded in different city spaces"--